Concept And Implementation of Pes Program in the Cidanau Watershed: A Lesson Learned for Future Environmental Policy - Budhi, Gelar Satya; SA, Kuswanto; Iqbal, Muhammad (Analisis Kebijakan Pertanian, 2008)
Objective of the paper is to depict the concept of PES (Payment for Environmental Services) and its implementation in the Cidanau Watershed. This paper is a success story of PES implementation starting from the early adoption of the concept. The study shows that PES has impressed by many institutions, which was then initiated by PT KTI (Krakatau Tirta Industri) as a pilot project of the concept implementation. The main practice of PES implementation activities was promoting conservation farming, including transfer of conservation technology and trees growing. The conservation farming showed good development, which was characterized by more trees planted, more conservation technology applied, and more optimistic expectation for income increase. Moreover, PES Program will not only attract the farmers who participated in the program, but also other farmers who were not included in it. With such promising performance, PES Program can potentially be adopted by farmers and provide solution to various problems encountered in the Cidanau Watershed.